Who’s afraid of Sahra – Understanding the shift in votes towards Germany’s Bündnis Sahra Wagenknecht - Leon Heckmann; L Constantin Wurthmann; Sarah Wagner (Research & Politics)
The emergence of the left-authoritarian Bündnis Sahra Wagenknecht (BSW) has profoundly disrupted the German party system. Within a remarkably short time frame, the BSW has achieved significant electoral success, prompting a lively debate concerning the political origins of its voter base. A central question remains: to what extent can the BSW attract supporters from other parties such as the Alternative for Germany (AfD) or Social Democrats (SPD)? This study employs recent data from the German Longitudinal Election Study (GLES) panel to investigate voter flow dynamics and the issues motivating shifts towards the BSW. Our findings reveal that while the BSW struggles to attract core AfD supporters, the party has been notably more effective in appealing to recent AfD supporters. Overall, opposition to Ukraine support is the single most important issue that drives voters towards BSW.